FINANCING LEVEL, MARGIN INCOME, AND PROFIT SHARING RATE WITH THIRD-PARTY FUNDS AS MODERATORING - Adilah Permananingrum (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Financing services are not limited to conventional financing, but also the concept of sharia which is currently developing very rapidly. Sharia-based financing is applied to Baitul-Mal wa at-Tanwil (BMT) which is growing in the community. The object of this study is BMT in Tegal City, with a purposive sampling method to determine the sample. The sample of this study was five BMT in Tegal city, with an observation period of five years (2016 to 2020). The data is used panel data, with a linear regression analysis method using the Eviews 10. This study aims to determine the level of financing affecting the level of profit sharing it receives, as well as to determine the margin income of murabahah affects the level of sharing results. As a result, the level of financing does not have a significant effect on the profit-sharing rate, but after including the moderation variable of third-party funds, the level of financing significant affects the profit-sharing rate. While murabahah margin income has a significant effect on profit-sharing rates, so do third-party funds added as a moderation variable murabahah margin income remains a significant effect on the profit-sharing rate.